Evaluation of Workplace Violence Against Physicians and Its Effects on Them - Usluoğulları, Fatih Hitami; Yurtseven, Nurşen Turan (The Bulletin of Legal Medicine, 2023)
Objective: One of the biggest problems that physicians face in their work life is the violence that they are exposed to. This study aims to determine the frequency and characteristics of the violence experienced by physicians in the workplace and to determine how the exposure to violence affects physicians’ job satisfaction, suicide risk, burnout levels.Methods: This study is a cross-sectional study with descriptive characteristics. Four hundred-eighteen volunteer physicians participated. The questionnaires distributed to the participants were reviewed with the literature and consisted of sociodemographic information, questions about violence, Minnesota Job Satisfaction Scale, Suicide Probability Scale, Maslach Burnout Scale. Results: It was observed that 58.4% of physicians were exposed to workplace violence during the last year and there was a significant difference in terms of gender, age, title, institution, duration of work and department. Physicians who suffered violence in the workplace during the last year; emotional exhaustion, insensitivity and suicide probability levels were higher, job satisfaction and personal success levels were lower than physicians who didn’t suffer.Conclusion: In order to prevent violence against health workers and physicians and to reduce their possible effects, changes in the health policies implemented, improvement of working conditions, reorganization of the health environment, especially in emergencies, and a deterrent law that the Turkish Medical Association has been expressing for years should be enacted.
Keywords: Physicians, Workplace Violence, Job Satisfaction, Burnout, Suicide